Redox‐Dependent Bone Alkaline Phosphatase Dysfunction Drives Part of the Complex Bone Phenotype in Mice Deficient for Memo1. (5th March 2018) - Moor, Matthias B; Ramakrishnan, Suresh K; Legrand, Finola; Dolder, Silvia; Siegrist, Mark; Durussel, Fanny; Centeno, Gabriel; Firsov, Dmitri; Hynes, Nancy E; Hofstetter, Willy; Bonny, Olivier
ABSTRACT: Mediator of ErbB2‐driven cell Motility 1 (MEMO1) is an intracellular redox protein that integrates growth factors signaling with the intracellular redox state. We have previously reported that mice lacking Memo1 displayed higher plasma calcium levels and other alterations of mineral metabolism, but the underlying mechanism was unresolved and the bone phenotype was not described. Here, we show that Cre/lox‐mediated MEMO1 deletion in the whole body of C57Bl/6 mice (Memo cKO) leads to severely altered trabecular bone and lower mineralization, with preserved osteoblast and osteoclast number and activity, but altered osteoblast response to epidermal growth factor (EGF) and FGF2. More strikingly, Memo cKO mice display decreased alkaline phosphatase (ALP) activity in serum and in bone, while ALPL expression level is unchanged. Bone intracellular redox state is significantly altered in Memo cKO mice and we inferred that ALP dimerization was reduced in Memo cKO mice. Indeed, despite similar ALP oxidation, we found increased ALP sensitivity to detergent in Memo cKO bone leading to lower ALP dimerization capability. Thus, we report a severe bone phenotype and dysfunctional bone ALP with local alteration of the redox state in Memo cKO mice that partially mimics hypophosphatasia, independent of ALPL mutations. These findings reveal Memo as a key player in bone homeostasis and underline a role of bone redox state in controlling ALP activity. © 2018 American Society for Bone and Mineral Research